2015
DOI: 10.1093/cvr/cvu264
|View full text |Cite
|
Sign up to set email alerts
|

Functional crosstalk between cardiac fibroblasts and adult cardiomyocytes by soluble mediators

Abstract: Fibroblasts have different roles during physiology and disease in regulating myocardial function via soluble mediators. A crosstalk between fibroblasts and cardiomyocytes, controlled by TGF-β, is crucial in this interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(123 citation statements)
references
References 44 publications
7
115
0
1
Order By: Relevance
“…Medium conditioned with cardiac fibroblasts isolated from pressure-overloaded rat hearts increased cardiomyocyte size, which was inhibited by transforming growth factor-β (TGF-β) type 1 receptor antagonist. 39 These results suggest that cardiac fibroblasts and adult cardiomyocytes communicate via paracrine networks (Figure ; Table).…”
Section: Cardiac Fibroblast-cardiomyocyte Paracrine Communications Inmentioning
confidence: 85%
“…Medium conditioned with cardiac fibroblasts isolated from pressure-overloaded rat hearts increased cardiomyocyte size, which was inhibited by transforming growth factor-β (TGF-β) type 1 receptor antagonist. 39 These results suggest that cardiac fibroblasts and adult cardiomyocytes communicate via paracrine networks (Figure ; Table).…”
Section: Cardiac Fibroblast-cardiomyocyte Paracrine Communications Inmentioning
confidence: 85%
“…Interstitial fibroblasts contribute to the biochemical, structural, and electromechanical properties of the myocardium, and are therefore are of particular interest for their major role in the development of cardiac fibrosis following their transdifferentiation into myofibroblasts [Brown et al, 2005;Camelliti et al, 2005;Weber et al, 2013;Travers et al, 2016]. TGFβ1 plays a critical role in myofibroblast transdifferentiation via Smad3 signaling [Bujak et al, 2007, Dobaczewski et al, 2010 and the upregulation of CTGF, FN, and collagen levels [Lijnen et al, 2000, Bujak et al, 2007 as well in directing CM hypertrophy and the cross-talk between CMs and CFs [Cartledge et al, 2015]. A limitation of this study is that we have not yet tested the effect of known antifibrotic agents on TGFβ1-stimulated fibrosis in VCSs.…”
Section: Discussionmentioning
confidence: 99%
“…In another study on the effects of fibroblast on cardiomyocytes, cardiomyocyte hypertrophy was observed. In that study it was demonstrated that transforming growth factor beta (TGFβ) had an bidirectional regulatory signaling role between the fibroblasts and cardiomyocytes[39]. Factors such as TGFβ are involved or expressed in response to hypertrophy and loss of adhesions.…”
Section: Discussionmentioning
confidence: 99%